STUDENTS' PERCEPTIONS OF RELATIONSHIPS AND ATTITUDES ABOUT FOOD SAFETY - Wan Ishak, Wan Mahasin; Ismail, Lisa Mariam Syawal; Zakariah, Siti Hajar; Ahmad, Nor Aziah; Tukiran, Nor Anis Intan Aqiah (Research and Innovation in Technical and Vocational Education and Training, 2023)
Safe food supplies are essential for the growth and stability of national economies, facilitating trade and tourism. The safe practices of handling, preparing, and storing can help to avoid food contamination and reduce foodborne illness. A study was carried out to identify the student's level of knowledge and attitudes about food safety practices used during online learning sessions. The study sample consisted of 92 students from Bachelor in Food Service Technology (BBS), from Year 1 and Year 2 programs who were randomly selected. Respondents from the Faculty of Technical and Vocational Education (FPTV), Universiti Tun Hussein Onn Malaysia (UTHM) as they have a basic knowledge of food preparation and attended online classes. A set of questionnaires was administered to assess students' basic knowledge and attitudes toward food safety as they were practiced throughout online learning sessions. The frequency, percentage, and mean score were calculated using the Statistical Package for Social Sciences version 26.0 software. The findings demonstrate that university students have a basic understanding of food safety (m=4.16). Not only that, a mean score of 4.25 shows that students have a positive attitude toward food safety principles practiced during the online learning sessions. Thus, we can conclude that having a solid foundation in food safety measures will affect positive attitudes toward food safety at home.